Pragmatic competence development in virtual environments in light of the COVID-19 pandemic in higher education in palestine - Shalhoub, Mona M. (IGI Global, 2023)
This chapter presents a study that investigated the perceptions of English as a foreign language (EFL) learners' pragmatic competence development in virtual environments in higher education in Palestine for the academic year 2020-2021 in light of COVID-19 pandemic. For this purpose, a mixed-methods approach was employed using a questionnaire, role-play, and semi-structured interview. Seventy-five undergraduate EFL learners from four universities participated in this study. Results of the quantitative phase revealed positive perceptions of EFL learners towards pragmatic competence development in virtual environments, with the majority of responses falling under the categories of agree or strongly agree. Responses to the role-play activity demonstrated that there were differences in the pragmatic aspects EFL learners employed in favor of females, particularly in the richness of linguistic resources and level of politeness. EFL learners acknowledged the importance of pragmatic competence as a means to successful communication and emphasized its teachability in formal instruction. © 2023, IGI Global. All rights reserved.